How can New Zealand schools respond to climate change? - Bolstad, Rachel (2020)
International climate agreements say education can play a key role in responding to the global challenge of climate change. My team and I are currently carrying out research to help build a national picture of educational responses to climate change. Our research suggests that New Zealand’s educational policies and strategies currently provide a diffuse framework for responding to climate change, and there is a lack of coherent messaging “from the top” about what could or should be expected of schools. Yet some innovative practices and approaches are visible across the school network. This article describes what we currently know about climate and sustainability thinking and practice across English-medium schools, and what further actions and supports may be needed across the system.
openalex: W3114429793 mag: 3114429793
Keywords: C:New Zealand; _z:class:countries; _z:class:themes; oa:keyword:climate change; oa:keyword:new zealand schools; oa:sdg:13 Climate action; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T11806 Impact of Service-Learning in Higher Education; openalex:import; openalex:yes